Development of the installation process for the tidal power plant Deep Green at Minesto AB - Christian, Andersson; Johannesson, Adam (My University, 2013)
The energy consumption on earth increases while the reserves of fossil fuels are running out and it is only a matter of time before we are dependent on renewable energy sources. Motion of water is an energy source containing a large amount of energy and to extract that energy out of tidal currents is one way to use it. There are power plants using the energy in the tidal currents today, but only close to land due to the shallow water and the high velocities. Minesto is a company that sees the potential in the currents with low velocities further from land where the space is not a problem. This is where they see the future for their concept Deep Green. Deep Green shortly consists of a kite equipped with a turbine that moves through the water in a shape of an eight to optimize the energy extraction at the low velocities. The electricity and signals are transferred from the kite through the tether and a bottom joint into a cable on the seafloor. A prototype in small scale is being tested at the coast of Ireland and currently there is no good solution for servicing the bottom joint. A bottom joint containing a universal joint, a swivel with slip rings transferring power, electricity and signals to the seafloor cable is needed. Therefore, a solution for the bottom joint’s design and attachment on the base has been investigated. The purpose is to lower, fit and elevate the bottom joint to enable service for 20 years with an maintenance interval of about 5 years for the first 10-20 produced power plants. This has been accomplished by doing research about the conditions at the seafloor, various offshore industries, equipment and techniques. Through these investigations in subsea engineering together with different methods for concept development, a final concept has been developed and visualized. In this final concept the bottom joint will be lowered from a vessel by the tether and be winched to the base through a motorized cable mounted on the bottom joint. The bottom joint will use a camera to ensure its position and to supervise the fitting. Three pins on the base will be fitted in conical holes on the bottom joint along with a stab plate to transfer electricity and signals. The bottom joint will be elevated by the tether for service every fifth year. A 3D-model of the concept has also been printed to verify the fitting No strength calculations are performed and the dimensions are only estimated since the concept is not developed for production.
Keywords: Maskinteknik; Mechanical Engineering